Assessment of Isometric Shoulder Strength in Swimmers: A Validation and Reliability Study of the ASH and iASH Tests - Hugo Ogando-Berea; Santiago Virgós-Abelleira; Pablo Hernandez-Lucas; Fernando Zarzosa-Alonso (Journal of Functional Morphology and Kinesiology)
Background/Objectives: Shoulder pain is one of the most common injuries among athletes who perform overhead movements. The Athletic Shoulder Test (ASH) has been validated to measure isometric shoulder strength in rugby and baseball players but has not yet been applied to swimmers, where the prevalence of shoulder pathologies reaches up to 91%. The present study aims to validate the ASH and Inverse Athletic Shoulder Test (iASH) in swimmers and establish general values for both tests. Methods: A total of 21 swimmers from the Galician and Asturian Swimming Federation were evaluated using the ASH and iASH tests, measuring strength in three positions (180°, 135°, and 90°). Relative reliability was analysed using the Intraclass Correlation Coefficient (ICC), absolute reliability was assessed through the Standard Error of Measurement (SEM) and Minimal Detectable Change at 90% confidence (MDC90), and variability was determined using the Coefficient of Variation (CV%), applying statistical tests such as Wilcoxon. Results: The ASH and iASH tests demonstrated excellent reliability (ICC = 0.9) across all positions, with acceptable variability (CV% < 35%). No statistically significant differences were found between the preferred and non-preferred side (p > 0.05), except in the iASH test at 180°, where a difference was observed (p = 0.007). The SEM values ranged from 4.39 to 7.39 N, while the MDC90 varied between 10.22 and 17.19 N, ensuring the tests’ sensitivity in detecting real changes in shoulder strength. Conclusions: The ASH and iASH tests are reliable tools for assessing shoulder strength in swimmers and can be used to monitor muscular imbalances and prevent injuries. The symmetry in strength between both sides supports their applicability in preventive programmes.